The Complicit Player: How Assassin’s Creed II, Bioshock and Dark Souls Use Narrative and Gameplay Design to Make the Player Complicit with the Actions of the Player-Character - Muggeridge, B.G.M. (2021)
This thesis proposes a model for analysing the process by which video games make players complicit in the actions of the player-character (avatar). Empathy, responsibility and desire are the formational elements of complicity and are the concepts I identify within three video games. Katherine Isbister’s proposed ‘levels of projection’ are also used to explain how a player relates to the player-character in order for the exchange of empathy, responsibility and desire to be effective. The games I have chosen to analyse are Assassin’s Creed II, BioShock and Dark Souls, each of which use gameplay and narrative design in unique ways to make players complicit.